Nano hydroxyapatite-blasted titanium surface affects pre-osteoblast morphology by modulating critical intracellular pathways - Bezerra, Fábio [UNESP]; Ferreira, Marcel R. [UNESP]; Fontes, Giselle N.; da Costa Fernandes, Célio Jr [UNESP]; Andia, Denise C.; Cruz, Nilson C. [UNESP]; da Silva, Rodrigo A. [UNESP]; Zambuzzi, Willian F. [UNESP] (Wiley, 2017)
Although, intracellular signaling pathways are proposed to predict the quality of cell-surface relationship, this study addressed pre-osteoblast behavior in response to nano hydroxyapatite (HA)-blasted titanium (Ti) surface by exploring critical intracellular pathways and pre-osteoblast morphological change. Physicochemical properties were evaluated by atomic force microscopy (AFM) and wettability considering water contact angle of three differently texturized Ti surfaces: Machined (Mac), Dual acid-etching (DAE), and nano hydroxyapatite-blasted (nHA). The results revealed critical differences in surface topography, impacting the water contact angle and later the osteoblast performance. In order to evaluate the effect of those topographical characteristics on biological responses, we have seeded pre-osteoblast cells on the Ti discs for up to 4 h and subjected the cultures to biological analysis. First, we have observed pre-osteoblasts morphological changes resulting from the interaction with the Ti texturized surfaces whereas the cells cultured on nHA presented a more advanced spreading process when compared with the cells cultured on the other surfaces. These results argued us for analyzing the molecular machinery and thus, we have shown that nHA promoted a lower Bax/Bcl2 ratio, suggesting an interesting anti-apoptotic effect, maybe explained by the fact that HA is a natural element present in bone composition. Thereafter, we investigated the potential effect of those surfaces on promoting pre-osteoblast adhesion and survival signaling by performing crystal violet and immunoblotting approaches, respectively. Our results showed that nHA promoted a higher pre-osteoblast adhesion supported by up-modulating FAK and Src activations, both signaling transducers involved during eukaryotic cell adhesion. Also, we have shown Ras-Erk stimulation by the all evaluated surfaces. Finally, we showed that all Ti-texturing surfaces were able to promote osteoblast differentiation up to 10 days, when alkaline phosphatase (ALP) activity and osteogenic transcription factors were up-modulated. Altogether, our results showed for the first time that nano hydroxyapatite-blasted titanium surface promotes crucial intracellular signaling network responsible for cell adapting on the Ti-surface.Biotechnol. Bioeng. 2017;114: 1888–1898. © 2017 Wiley Periodicals, Inc.
Keywords: adhesion; biotechnology; hydroxyapatite; implants; nanotechnology; osteoblast; signal transduction